A higher call - Makos, Adam (Berkley Books, 2013)
This is the true story of the two pilots whose lives collided in the skies over wartime Germany on 21 December 1943 --the American--2nd Lieutenant Charlie Brown, a former farm boy from West Virginia who came to captain a B-17--and the German--2nd Lieutenant Franz Stigler, a former airline pilot from Bavaria who sought to avoid fighting in World War II.